Difficulties in applying the Montessori method in kindergartens from the point of view of kindergarten educators (A field study in the city of Lattakia) - درويش, سمر; مطيعة أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The current research aimed at the difficulties of applying the Montessori method in kindergartens from the point of view of kindergarten educators. The research sample consisted of (152) private kindergarten educators in the city of Lattakia for the academic year 2022/2023. The researcher adopted the descriptive approach, and used the questionnaire as a research tool, consisting of (30) phrases, distributed on two axes: (difficulties related to educators, and difficulties related to the educational environment), and an open question about proposals for applying the Montessori method in kindergartens from the educators' point of view. The current research found the following: -The degree of difficulties in applying the Montessori method in kindergartens from the point of view of kindergarten educators in the city of Lattakia was high. - There are no statistically significant differences in the viewpoints of kindergarten educators about the difficulties of applying the Montessori method in kindergartens according to the variable number of years of experience and training courses for the educator. - There are no significant and essential differences between the responses of the research sample individuals about the difficulties of applying the Montessori method in kindergartens according to the educational and scientific qualification variable related to the educational environment in the kindergarten, while there were significant and essential differences at the level of the total score of the questionnaire, and at the axis of the difficulties related to nannies in the kindergarten in favor of High school or middle school campaign.